Aging characteristics and reactivity of two types of nanoscale zero-valent iron particles (FeBH and FeH2) in nitrate reduction - Kim, Hong-Seok (2013)
The reactivity towards nitrate and aging characteristics of two types of Fe nanoparticles (FeBH and FeH2 nanoparticles) were investigated. During shell modification for producing air-stable Fe nanoparticles, the shell layers of FeBH nanoparticles were passivated more extensively than those of FeH2 nanoparticles were. Column experiments showed that the nitrate-reduction capacity of FeBH nanoparticles was 35 times higher than that of FeH2 nanoparticles. The Fe(0) core of FeBH nanoparticles was consumed completely before breakthrough during the nitrate-reduction column experiments, which indicates that the thickness of FeBH nanoparticles’ shell layers remained constant during aging. The FeH2 nanoparticle surfaces were readily passivated, and subsequently depassivated and reactivated by acid flushing, which indicates that the thickness of FeH2 nanoparticles’ shell layers increased during aging. Exhausted nanoparticles were examined to obtain information on equilibrium mineral phases. Magnetite was prevalent among the mineral phases in the exhausted FeBH nanoparticles, unlike in the case of the FeH2 nanoparticles. The formation of goethite as an aging product of FeBH nanoparticles is reported for the first time herein. Conceptual aging models for FeBH and FeH2 nanoparticles are proposed on the basis of current and previous experimental results.